Budaya Di Era Digital: Peran Tekonologi Dalam Mempengaruhi Budaya dan Pola Komunikasi Masyarakat - Purwanto, Eko; Salsabila, Farah Lutfiya; Khaeriah, Ade Siti; Sagita, Della Nesha; Setiawati, Heni (Universitas Bina Sarana Informatika, 2025)
Abstract - Technology is the overall means used to provide goods necessary for human survival and human comfort. In the digital era, technology has developed at an accelerated pace. One of the most prominent aspects of the changes that occur in human life and make all human activities from manual to digital is technology. The purpose of this article is to explain how technology affects the culture and communication patterns of society, as well as the challenges and opportunities that will be faced by society in the era of digital technology. The influence of technology on human life is pervasive, particularly in the domains of culture and communication. In the digital era, technology has made it easier for individuals to perform daily activities, which has led to social changes. These changes can be beneficial or detrimental, depending on their nature and the context in which they occur. The positive influence of technology on culture and communication patterns is evident in the ease of long-distance communication and the preservation of local culture through the use of online media from various platforms. However, the negative effect is the potential loss of traditional values due to advances in information and communication technology. Furthermore, the digital era presents both challenges and opportunities for communities as a result of the influence of technology on culture and communication patterns. Keywords: technology, digital, culture, communication patterns, society, impact